THE UKRAINIAN SPIRITUAL MUSIC IN THE PROFESSIONAL TRAINING OF THE MUSIC TEACHERS - Kyfenko., А. (Continuing Professional Education: Theory and Practice, 2023)
The Ukrainian spiritual choral music as a powerful tool of regulation choir members humanistic value relationships and their spiritual and moral qualities was considered in the article. Deals with highlights of the importance of the Ukrainian spiritual choral music in academic choir repertoire. Author determined the essence of spiritual choral music, characterized the significance of spiritual singing impact on identity formation. Such modern art connoisseurs as N.O. Gerasymova-Persydska, I.F. Lyashenko, P.I. Sikur, S.I. Ulanova, M.S. Yurchenko prove that spiritual music is one of the main components of art culture and fixing the characteristics of objectification content of outlook bases. It is like type of art mediates a general cultural dominant of society, reveals all the signs of its spiritual life, intellectual and social-psychological potential. The religious choral works of Ukrainian composers were considered in terms of didactics and morals, which are an integral part of the academic choir repertoire. Ukrainian spiritual choral music is high moral, didactic stratum, a large value of the world of art that makes you to think, to empathize, to analyze. The repertoire of the student choir must to include the best examples of Ukrainian choral school such as «Liturgy» of D. Bortnyansky, works of M. Berezovsky, A. Vedel, D. Dyletsky, M. Leontovych, K. Stetsenko, Kiev-Pechersky chant works, choral music of Ukrainian modern composers works: L. Dychko, I. Eletskiy, B.Filts, M. Shuha, O.Yakobchuk, E. Stankovich, who is the foundation of high morality and one of the reasons formation of the mental world and the outlook of the personality.